Influence of post-etching surface treatment and thermo-mechanical cycling on fracture strength of ceramics - Cotes, Caroline [UNESP]; Zogheib, Lucas; MaCedo, Vanessa [UNESP]; Carvalho, Rodrigo [UNESP]; Martinelli, Carolina [UNESP]; Kimpara, Estevão [UNESP] (My University, 2016)
BACKGROUND: The aim of this study was to evaluate fracture strength of lithium disilicate-based ceramic crowns submitted to neutralization of hydrofluoric acid (HF) precipitates associated with ultrasonic bath and to thermo-mechanical cycling. METHODS: Eighty human molars received conventional full crown preparation after being included in polyurethane standard to simulate periodontal ligament. After scanning, the ceramic blocks were machined using CA D/CA M system to obtain the crowns. The crowns were distributed according to surface treatment: S and S-C; HF and silane; SNU and SNU-C; HF neutralization of HF precipitates, ultrasonic bath and silane. The crowns were cemented with dual cure resin cement and the specimens in Groups S-C and SNU-C were submitted to thermo-mechanical cycling (5/55 °C/60 s while 1.2 million mechanical cycles of 4 Hz/100 N). The samples were submitted to compressive test. Analysis of fractures was performed macroscopically (Burke method) and using Scanning Electron Microscope. The data of fracture strength were analyzed using the two-way ANOVA. RESULTS: No statistical difference among the groups was found (p-value = 0,799). Most failures were associated with the remaining tooth fracture and the fracture origin was located on the cementation surface. CONCLUSIONS: Postetching cleaning protocols do not improve the fracture strength of ceramics crowns. Thermo-mechanical aging did not weakened the ceramic crown.